Temperature simulation and experimental for polishing TC4 with abrasive cloth wheel - Libo WANG; Chao XIAN; Hongmin XIN (Jin'gangshi yu moliao moju gongcheng)
ObjectivesDuring the polishing and grinding process, a large amount of heat is generated in the contact area between the grinding tool and the workpiece, while the amount of material removed is very small. Most of the heat is transferred to the workpiece, causing a rapid increase in temperature near the surface of the workpiece. This results in adverse effects such as residual tensile stress, white layer, and deformation, which negatively impact the surface quality and performance of parts. Therefore, studying the distribution laws and influencing factors of surface temperature in polishing and grinding, and controlling the processing surface temperature are of great significance.MethodsA polishing test platform is built, and polishing temperatures are measured under different process parameters. The measured temperature values are corrected to obtain the actual temperature values. A theoretical model of the temperature field in the polishing contact area is derived based on the rectangular moving heat source model, and a temperature calculation model corresponding to the experimental measurement point is obtained, with the temperature value of that point calculated. The workpiece temperature field distribution during polishing is obtained using ANSYS simulation software and APDL for cyclic loading. The distribution law of the workpiece temperature field is studied, and the internal mechanism of this distribution law is explored. The temperature values corresponding to the experimental measurement points are extracted. The measured, calculated, and simulated values of temperature near the same point in the polishing contact area are compared. Based on the experimental results, single factor influence law figures of four process parameters on polishing temperature are drawn, and the influence mechanisms of the four process parameters on polishing temperature are explored. Based on the relationship between the radius increment and compression depth of abrasive cloth wheel, flexible polishing and rigid polishing are defined, and the effects of flexible and rigid polishing on polishing temperature are explored. A main effect analysis of process parameters is conducted with polishing temperature as the response and process parameters as the factors, to study the degree of influence of each process parameter on polishing temperature. ResultsComparing the measurement results, calculation results, and simulation results of polishing temperature, it is found that the deviation rates between the simulation values and the measurement values are less than 22%, and the devia-tion rates between the calculated values and the measurement values are less than 17%. The deviations between simu-lated values and measured values are mainly due to the actual heat source model being complex, while the simulated heat source model uses a simplified rectangular heat source model, as well as measurement errors. The deviations between calculated and measured values are mainly caused by measurement errors in contact arc length, temperature, heat distribution coefficient, and the heat source model. The influence of four process parameters on polishing temperature is as follows: polishing temperature increases with the increase of spindle speed, because higher spindle speed results in greater linear velocity of the abrasive cloth wheel, and more work is done by the frictional force between the abrasive particles, binder, and workpiece per unit time, generating more heat and resulting in higher polishing temperature; polishing temperature increases with the increase of the compression depth of the abrasive cloth wheel. This is because larger compression depth leads to greater tangential force on a single abrasive particle, and more abrasive particles participate in cutting. More work is done by the frictional force between the abrasive particles, binder, and workpiece per unit time, generating more heat, and resulting in higher polishing temperature; polishing temperature decreases with the increase of feed rate. Although higher feed rate enhances heat source intensity, the contact time between the workpiece and the heat source is shorter, resulting in less heat transferred to the workpiece and lower polishing temperature; polishing temperature decreases with the increase of mesh number of abrasive particles. This is because a larger mesh number of abrasive particle means smaller abrasive particle size and more abrasive particles interacting with the workpiece in the contact area, making heat more easily carried away by the abrasive particles. At the same time, the larger the mesh number of abrasive particle, the smaller the abrasive particle size, the larger the contact area between the workpiece and grinding tool, the smaller the tangential force exerted on a single abrasive particle, and the less work done by frictional force between the abrasive particle and the workpiece per unit time, generating less heat. These two reasons together lead to a decrease in polishing temperature with the increase of mesh number of abrasive particles. A main effect analysis shows that compression depth has the largest main effect and the greatest influence on polishing temperature, while the other three process parameters have smaller main effects and less influence on polishing temperature. ConclusionsThe value of compression depth has the greatest influence on the polishing temperature and also affects whether the polishing state is rigid or flexible. Therefore, when determining the polishing process parameters, the appropriate compression depth should be selected first, and then other process parameters should be selected accordingly.